A validation study of a Kinect based Body Imaging (KBI) device system based on ISO 20685:2010 - Bragança, S. (2014)
To replace the traditional anthropometric data collection processes with the 3D acquiring system it is important that the validity of the data is not compromised. To do this, a validation study, based on the guideline of ISO 20685, can be performed. This paper presents the results of a comparison between traditional measurements and measurements taken with a 3D acquiring system using only four Kinect sensors. The results obtained were then compared with the maximum allowable error indicated in ISO 20685, concluding that this system cannot give sufficiently reliable data that can substitute the manual procedures.